God, Religion, and War: Language, Concept, and the Problem of Definition from Genesis to Jihad to Levinas - Soltes, Ori Z. (Religions, 2023)
Using a discussion of the etymology of re-lig-io as a starting point, this essay begins by considering the problem of religion—of understanding God, and of language as an instrument for achieving the ends of religion and that understanding—and the problem for religion of revelation and interpretation. It follows to the consequences of this double complication for understanding “war” in the biblical and early Christian traditions. The essay leads, then, to a tri-valent discussion of “jihad”, and from this jihad centerpiece toward further versions of these complications as they apply to mysticism, medieval Jewish thought and thence toward and into modernity, from Spinoza to Levinas.